EFEKTIVITAS KINERJA BADAN NARKOTIKA NASIONAL KABUPATEN HULU SUNGAI UTARA DALAM UPAYA PENYALAHGUNAAN NARKOBA DI KALANGAN REMAJA KOTA AMUNTAI - Budiman, Arif (Al Iidara Balad, 2020)
Problems in the North Hulu Sungai Regency regarding drug trafficking have greatly increased, because it is the second largest area in South Kalimantan. And patient data that has been counseled by the National Narcotics Agency of North Hulu Sungai Regency as many as 29 people, but there are many more that have not been officially recorded. The purpose of this study was to identify and analyze the effectiveness of the performance of the National Narcotics Agency of the North Hulu Sungai Regency and the factors that influence the efforts to tackle narcotics abuse among Amuntai City teenagers. The research method is descriptive qualitative, type and source of data that is primary data through observation, interviews while secondary data through documents that exist at the National Narcotics Agency of North Hulu Sungai Regency with a sampling technique that is purposive sampling technique. From the results of the study showed that the effectiveness of the National Narcotics Agency of North Hulu Sungai District has been going well with various prevention efforts undertaken by the North Hulu Sungai Regency National Narcotics Agency in the efforts to Prevent and Eradicate Abuse and Circulation of Narcotics Darkness (P4GN) by going through Desire, Business in the form of socialization activities to various schools, universities or colleges, Communication and skills in the form of art performances; dissemination through print media, electronic media, and outdoor media; the formation and training of anti-drug cadres; in the efforts of P4GN BNNK Hulu Sungai Utara to implement the formation of work discipline to improve the performance of HNN North River North BNNK employees in eradicating Narcotics among the Community and adolescents by using measuring work discipline and work performance. Factors that affect the effectiveness of the performance of the North Narcotics National Narcotics Agency (BNNK) can be viewed from legal factors, facilities and facilities factors in law enforcement, community factors. The advice given for input material is to provide a place for counseling and rehabilitation for drug abusers among adolescents and the community, and to provide a funding budget that suits your needs